2010
DOI: 10.3126/jiom.v32i1.3996
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of penicillin resistant <i>Neisseria gonorrhoeae</i>

Abstract: Introduction: Since the beginning of the modern chemotherapeutic era, the treatment of gonorrhea has been dogged by the shifting antimicrobial susceptibility of Neisseria gonorrhoeae. Though penicillins have been recommended for treatment of gonorrhoeae, there have been reports of treatment failure with penicillins. In this study, we report the emergence of penicillin resistance N. gonorrhoeae and its antimicrobial susceptibility pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…In this study all isolates were 100 % susceptible to ceftriaxone which was analogous to 100 % susceptibility reported in Nepal [ 26 ], India [ 27 ], Brazil [ 28 ], Tanzania [ 20 ] and Ethiopia [ 6 ]. Our finding was also comparable to 99 % susceptibility towards the same antibiotic documented in Bangladesh [ 22 ].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In this study all isolates were 100 % susceptible to ceftriaxone which was analogous to 100 % susceptibility reported in Nepal [ 26 ], India [ 27 ], Brazil [ 28 ], Tanzania [ 20 ] and Ethiopia [ 6 ]. Our finding was also comparable to 99 % susceptibility towards the same antibiotic documented in Bangladesh [ 22 ].…”
Section: Discussionsupporting
confidence: 80%
“…In this study, N. gonorrhoeae isolates showed alarming rate (28.6 %) of resistance against ciprofloxacin which is higher than 18 % resistance to the same drug reported in Ethiopia [ 6 ], 20 % in Nepal [ 26 ], 21.4 % in Brazil [ 28 ] and 23.3 % in Uganda [ 23 ]. Such relative high rate of resistance seen in this study might be due to easly availability, indiscriminate and intensive use of this antibiotic in all health facilities in the country.…”
Section: Discussionmentioning
confidence: 69%
“…Studies on antibiotic resistance against sexually transmitted infections remain limited in Nepal. However, few identified studies reported high rate of resistance of Neisseria gonorrhoeae to antibiotics penicillin, tetracycline, and ciprofloxacin [ 70 - 72 ].…”
Section: Antimicrobial Resistance Of Various Microbial Pathogensmentioning
confidence: 99%
“…Antibiotic sensitivity pattern for N. gonorrhoea in different part of the world is also not uniform, and the emergence of resistance to the commonly used drugs, such as penicillin, tetracycline and ciprofloxacin is frequent in different part of the world including South East Asian Region (SEAR) [4]. During 2009-12, the percentage of penicillinase producing N. gonorrhoeae (PPNG) isolates from WHO.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of gonococcal infection varies greatly among countries in the developed and developing world, the highest being in South and Southeast Asia, followed by sub-Saharan Africa and America. According to the World Health Organization, there are approximately 62 million new cases of gonorrhoea worldwide annually, and almost half of the cases are estimated to occur in Southeast Asia [3] [4]. High rate of prevalence of gonorrhoea is due to presence of a large reservoir of asymptomatic carriers in the community and development of antimicrobial resistance to N. gonorrhoea [1] [5].…”
Section: Introductionmentioning
confidence: 99%